2018
DOI: 10.4315/0362-028x.jfp-17-106
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Preferences for Interventions To Reduce Microbiological Contamination in Dutch Vegetable Production

Abstract: Understanding growers' preferences regarding interventions to improve the microbiological safety of their produce could help to design more effective strategies for the adoption of such food safety measures by growers. The objective of this survey study was to obtain insights for the design of interventions that could stimulate growers to increase the frequency of irrigation water sampling and water testing to reduce possible microbiological contamination of their fresh produce. The results showed that price i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 13 publications
0
2
0
1
Order By: Relevance
“…The weights for the nine criteria did not greatly differ, which explain why the overall ranking of the technologies was not influenced by the weights of the criteria. However, a study by Van Asseldonk et al (2018) showed that a grower's willingness to implement a technology is steered by price intervention (discounts and economic incentives). When cost is taken as the only criterion for selection, UV, sand filtration þ UV, US þ UV and chlorine dioxide were the top four disinfection technologies.…”
Section: Discussionmentioning
confidence: 99%
“…The weights for the nine criteria did not greatly differ, which explain why the overall ranking of the technologies was not influenced by the weights of the criteria. However, a study by Van Asseldonk et al (2018) showed that a grower's willingness to implement a technology is steered by price intervention (discounts and economic incentives). When cost is taken as the only criterion for selection, UV, sand filtration þ UV, US þ UV and chlorine dioxide were the top four disinfection technologies.…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al analyzed the understanding of Chinese customers' perceptions of nonthermal processing technologies and ways to mitigate negative perceptions [6]. Asseldonk et al found that understanding growers' preferences regarding interventions to improve the microbiological safety of their production could help to design more effective strategies for the adoption of such food safety measures by growers [7]. Regulations and specifications on processing technology in the food industry could improve product quality and customer trust [8] and could affect the expected price in the spot markets [9].…”
Section: Relevant Literaturementioning
confidence: 99%
“…Geralmente consumidos crus, não recebem tratamentos específicos para minimizar possíveis riscos à saúde. Ocorre que boas práticas de manipulação dos alimentos agrícolas são fundamentais para gerenciar a segurança alimentar, como descrevem os estudos de van Asseldonk et al (2018) e Rajkumar (2010), entre outros. Por essa razão, leis são necessárias para garantir a qualidade dos produtos e estabelecer padrões de produção agrícola (Adalja & Lichtenberg, 2018).…”
Section: Introductionunclassified